Legal Politics Aspect of Regulation, Efforts of Safeguard, Supervision, and Control Over the Comercial Explosives in Indonesia - Fajar Pratama (Jurnal Dinamika Hukum, 2019)
The consequence of Indonesia as a state of law in accordance with Article 1 Paragraph (3) of the Constitution 1945 is that it creates legal politics which continues to develop in accordance with the dynamics of political life in the Indonesia state. Legal politics that has occurred in Indonesia was when the reform movement emerged demanding the separation of the Indonesian National Police and the TNI which had long been integrated into the Indonesian Armed Forces. Based on this incident, it has an impact on the regulation of Commercial Explosives in Indonesia according to the Decree of the President of the Republic of Indonesia Number 125 of 1999 about Explosives, with licensing arrangements generally still being issued by the Ministry of Defense of the Republic of Indonesia. However, the technical licensing arrangements for Commercial Explosives in Indonesia have been issued by the Police of the Republic of Indonesia.Keywords: legal politics, reform, commercial explosives, regulation